Iron and cobalt mononitrosyls with schiff base co-ligands / Hadariah Bahron - Bahron, Hadariah (2002)
The ligand N-4-methoxybenzylsalicylideneimine (MeObsal) is reacted with Fe2+ and Co2+ions separately. Both the systems are then reacted with nitric oxide (NO) to form two different complexes which are bis(N-4-methoxybenzylsalicylideneiminato)nitrosyliron, [Fe(MeObsal)2NO]; and bis(N-4-methoxybenzylsalicylideneiminato)nitrosylcobalt, [Co(MeObsal)2NO]. Both the complexes are microanalysed and subjected to infrared spectroscopy investigation and magnetic measurement. From the infrared investigation, [Fe(MeObsal)2NO] is found to exhibit an NO stretching frequency, VNO, at 1777 cm-I whereas [Co(MeObsal)2NO] shows VNO at 1640 cm-I. These values suggest that the iron nitrosyl complex contains linear Fe-N-O bond and the cobalt nitrosyl complex contains bent Co-N-O bond. The room temperature effective magnetic moment of [Fe(MeObsal)2NO] is measured to be 3.97 B.M. indicative of the presence of 3 unpaired electrons. The value shows that [Fe(MeObsal)2NO] is a high spin {Fe(NO)} system. However, the complex [Co(MeObsal)2NO] gives an effective magnetic moment of 0.91 B.M. indicating that there are no unpaired electrons present in this complex. It can be concluded that [Co(MeObsal)2NO] is a low spin {Co(NO)}8